High tension lines: Negative social exchange and psychological well-being in the context of instant messaging. (April 2019) - Tsai, Hsin-yi Sandy; Hsu, Pei-Jung; Chang, Chih-Ling; Huang, Chun-Cheng; Ho, Hsin-Fang; LaRose, Robert
Abstract: Instant messengers (IM) mediate several types of negative social exchanges that can affect the psychological well-being of their users. Using an instant messenger popular in Taiwan (LINE) as an example, this study examined the relationship between IM communication and well-being. An online survey was conducted and found that negative IM social exchanges in which messages were ignored by their recipients, interfered with other activities, or contained hostility or ridicule were directly related to a global measure of negative social exchange that included face-to-face as well as online interactions. Insensitive IM social exchanges were positively related to loneliness, depression, and fear of missing out (FoMO), and were negatively related to social support. Highlights: Insensitive IM social exchanges were positively related to loneliness and depression. Insensitive IM social exchanges were positively related to fear of missing out. Insensitive IM social exchanges were negatively related to social support. IM hostility was positively related to loneliness and depression. IM ridicule was positively related to loneliness and depression.